Operational stabilization of fungal α-rhamnosyl-β-glucosidase by immobilization on chitosan composites - Piñuel, Maria Lucrecia (2011)
The diglycosidase α-rhamnosyl-β-glucosidase from Acremonium sp. DSM24697 was immobilized by adsorption and cross-linking. The supports screened included beads of chitosan composites (gelatin, arabic gum, silica gel), epoxy-activated agarose and chitosan, and macroporous polyvinyl-alcohol cryogel. The chitosan-silica gel beads were selected because of the highest immobilization efficiency obtained and their morphological properties (diameter 1.67 ± 0.99 mm, circularity 0.81 ± 0.05). The optimization of the immobilization - coating with polyethyleneimine, changes in the enzyme load - improved the immobilization efficiency up to 18%. The practical use of the enzyme deals with low water solubility substrates. The higher KM for the immobilized enzyme - 8 mM vs. 1.8 mM hesperidin for the free enzyme - indicated that substrate diffusion limits the enzymatic reaction. The solvent dimethylsulfoxide (50%, v/v) was added in order to increase the substrate solubility, and 80% activity was retained (1 h, 60 °C) in contrast with the complete inactivation of the free form. The stability of the immobilized catalyst was extended to metal catalyzed oxidation where the enzyme was fully preserved in harsh conditions such as 1 mM CuSO4 at 60 °C during 1 h.